Bacterial contamination in a modern operating suite. 3. Importance of floor contamination as a source of airborne bacteria. - Hambraeus, A. (Cambridge University Press, 1978)
The redispersal factor for bacteria-carrying particles from a contaminated floor was determined after mopping, blowing and walking activity. Walking gave the highest redispersal factor, 3.5 X 10(-3) m-1, which was three times higher than for blowing and 17 times higher than for mopping. The mean die-away rate for the bacteria-carrying particles used was 1.9/h without ventilation and 14.3/h with ventilation. It was calculated that in the operating rooms less than 15% of the bacteria found in the air were redispersed floor bacteria.